Urinary Bladder and Posterior Urethral Morphology in Voiding Cystourethrogram and Its Implications in Management and Prognosis of Posterior Urethral Valves - Manita Tamang; Manoj Kumar Mohanty; Aditya Arvind Manekar; Subrat Kumar Sahoo; Bikasha Bihary Tripathy (Journal of Indian Association of Pediatric Surgeons)
Aims: The most frequent cause of bladder outlet obstruction in children is posterior urethral valves (PUVs). The diagnosis of PUV is made by visualization of the valve by cystoscopy, and for documenting PUV, voiding cystourethrogram (VCUG) remains the gold standard imaging method. VCUG metrics such as height and width of the posterior urethra (HW-PU), HW of bladder, and PU-to-anterior urethra ratios (PU-AU ratios) are employed separately in a number of research. In our study, we have attempted to analyze the initial VCUG using various morphological ratios and prognosticate the same using a proposed scoring system. Methodology: All diagnosed cases of PUV presenting to the department of pediatric surgery who have undergone primary ablation (January 2023 to June 2024) were included. The creatinine level just before valve ablation was recorded. VCUG was done as per the standard protocol, and various morphological ratios were recorded. Again, serum creatinine and VCUG were repeated after 3 months, and the score was compared to prognosticate the renal outcome. Results: A total of 45 boys were ablated at a mean age of 10.21 (17.41) months and followed up for 6 months. The mean serum creatinine (mg/dL) decreased from 0.89 to 0.64 after 6 months of ablation. This change was statistically significant. PU:AU, bladder height (BH):bladder width (BW), and BN:PU change were significant (P < 0.005); however, WPU:HPU change was not statistically significant (P = 0.183). Conclusions: This study provides evidence that specific VCUG morphological ratios, particularly PU:AU and BH:BW, are valuable in assessing the effectiveness of valve ablation in PUV patients and can serve as reliable indicators of improved renal function.